2015
DOI: 10.18270/rsb.v1i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Charles Bonnet

Abstract: En la medida que crece la población y aumenta el número de personas de la tercera edad con trastornos de la visión, se necesita cada vez más hacer conciencia del Síndrome de Charles Bonnet entre los oftalmólogos, psiquiatras y neurólogos. El propósito de la presente revisión es ofrecer una visión actualizada sobre sus aspectos clínicos, fisiopatológicos, epidemiológicos junto con las estrategias de manejo más razonables. Para ello se emprendió una búsqueda exhaustiva de la literatura más relevante, con el fin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Based on these findings, it was suggested that elderly people, when suffering vision loss, could develop compensations in these areas, which could contribute to the emergence of symptoms. However, in this study, no significant activation of the primary visual cortex compared to the visual association cortex was observed (3).…”
Section: Pathophysiologycontrasting
confidence: 79%
See 3 more Smart Citations
“…Based on these findings, it was suggested that elderly people, when suffering vision loss, could develop compensations in these areas, which could contribute to the emergence of symptoms. However, in this study, no significant activation of the primary visual cortex compared to the visual association cortex was observed (3).…”
Section: Pathophysiologycontrasting
confidence: 79%
“…Most cases are described in the elderly population aged 70 to 93 years, with no difference between male and female sexes and associated with visual loss due to degenerative processes (3,1). Although SCB is not rare in patients with visual deficits, its description in ophthalmological publications is unusual, perhaps due to the lack of knowledge about this entity by most ophthalmologists (7).…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations